Nilai-Nilai Estetika Melayu dalam Lirik Lagu Karya Rhoma Irama Kajian terhadap Lirik Lagu “Seni” dan “Buta Tuli” - Moh. Muzakka (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2020)
The purpose of this research is to reveal the aesthetic values in the lyrics of the song by Rhoma Irama, especially in the lyrics of the song